Validitas dan Praktikalitas E-Modul Berbasis Guided Inquiry disertai Virtual Laboratory pada materi Sistem Pencernaan untuk Memberdayakan Keterampilan Berpikir Kritis - Natalia Ravista; Sutarno Sutarno; Harlita Harlita (Postgraduate, University of Mataram, 2021)
This study aims to determine the validity and practicality of guided inquiry-based e-modules accompanied by virtual laboratories on digestive system materials to empower critical thinking skills. The type of research used is research and development (R&D), by applying the Borg and Gall development model consisting of 10 steps and grouped in four stages including: preliminary study stage, development, testing, and deployment. This study is limited to e-modules validity and practicality testing. The instruments used are the validity and practicality questionnaires. The assessment of the results of the validity and practicality questionnaire is interpreted with the likert scale. Based on the analysis of the data obtained the following results: 1) Test validity by material experts, learning device experts, media experts, and education practitioners obtained a value in a row that is, 85.30%, 95.40%, 88.30%, and 93.20% with very good category, 2) Practicality tests by small-scale student groups, large-scale student groups, and biology teachers from 3 schools obtained consecutive grades, i.e., 87.60%, 89.50%, and 90.00% with very good category. Based on the validity and practicality tests, it can be concluded that the e-modules developed are valid and practical to use